PENGARUH KOMPETENSI, PENGALAMAN, PROFESIONALISME DAN ETIKA AUDITOR TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK (KAP) KOTA MAKASSAR - rospi yanti (Jurnal Ilmiah Manajemen "E M O R", 2021)
Rosfianti M.Yadasang 2017   This study aims to determine the effect of competence, experience, professionalism and ethics of auditors on audit quality in KAP Makassar.This study aims to determine the effect of competence, experience, professionalism and ethics of auditors on audit quality in KAP Makassar. The sample used as many as 31 respondents, auditors found in 4 KAP in Makassar.  Data collection method used is by questionnaire. Data analysis methods used are descriptive statistics, test data quality, classic assumption test, and hypothesis testing.In test hypotheses using multiple regression analysis. This penlitian results show that the competence, experience, professionalism and ethics of auditors partially positive effect on audit quality auditor On KAP Makassar. Keywords: Competence, experience, professionalism, ethics of auditors, audit quality